2013
DOI: 10.1128/jvi.00843-13
|View full text |Cite
|
Sign up to set email alerts
|

Rabbit Anti-HIV-1 Monoclonal Antibodies Raised by Immunization Can Mimic the Antigen-Binding Modes of Antibodies Derived from HIV-1-Infected Humans

Abstract: The rabbit is a commonly used animal model in studying antibody responses in HIV/AIDS vaccine development. However, no rabbit monoclonal antibodies (MAbs) have been developed previously to study the epitope-specific antibody responses against HIV-1 envelope (Env) glycoproteins, and little is known about how the rabbit immune system can mimic the human immune system in eliciting such antibodies. Here we present structural analyses of two rabbit MAbs, R56 and R20, against the third variable region (V3) of HIV-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 61 publications
(93 reference statements)
2
36
0
Order By: Relevance
“…The orthologue of the human VH5-51 gene segment in rhesus macaques is VH5.7, used by one of our V3-specific MAbs, GE2.JF11. Studies of V3-directed MAbs elicited in Env-immunized rabbits resulted in the isolation of the R56 MAb, which binds by the cradle mode via an epitope that overlaps with peptide 5 identified as the target epitope in our current study (31, 65). R56 was shown to neutralize a similar set of viruses as the V3-specific rhesus MAbs isolated here, suggesting that the V3-specific MAbs identified in our study bind by a similar mode of recognition.…”
Section: Discussionmentioning
confidence: 76%
“…The orthologue of the human VH5-51 gene segment in rhesus macaques is VH5.7, used by one of our V3-specific MAbs, GE2.JF11. Studies of V3-directed MAbs elicited in Env-immunized rabbits resulted in the isolation of the R56 MAb, which binds by the cradle mode via an epitope that overlaps with peptide 5 identified as the target epitope in our current study (31, 65). R56 was shown to neutralize a similar set of viruses as the V3-specific rhesus MAbs isolated here, suggesting that the V3-specific MAbs identified in our study bind by a similar mode of recognition.…”
Section: Discussionmentioning
confidence: 76%
“…The different groups of rabbits receiving clade C Env immunogens also produced primarily the V3C-type Abs. A recent study reported that one of the two anti-V3 crown mAbs isolated from a rabbit immunized with the HIV Env gp120 JRFL (clade B) using a DNA prime-protein boost regimen binds to its epitope in a V3C-binding mode [23]. The frequencies of V3L responders are also unlikely determined by the GPGR motif typically present in clade B Envs [38] .…”
Section: Discussionmentioning
confidence: 99%
“…S6A). Rabbits may be preferable as small animal models (Pan et al, 2013; Pinheiro et al, 2011) because they lack this serum background problem and also react better with conserved targets that may ultimately be important for the development of nAbs of any breadth. However, it is important to point out that the VH family diversity in both rabbits and guinea pigs is quite limited compared to primates and that their antibody diversity is generated principally by gene conversion, contrasting with the largely combinatorial origins of IgG diversity in primates (somatic hypermutation is also used in all cases).…”
Section: Discussionmentioning
confidence: 99%